The development of a conceptual model and self-reported measure of occupational health and safety vulnerability. (September 2015) - Smith, Peter M.; Saunders, Ron; Lifshen, Marni; Black, Ollie; Lay, Morgan; Breslin, F. Curtis; LaMontagne, Anthony D.; Tompa, Emile
Highlights: In combination with a variety of stakeholder groups we developed a definition for the concept of OH&S vulnerability that moved beyond hazard exposure in isolation. We conducted a rigorous process to develop a survey instrument congruent with this definition. The resulting 29-item measure displayed good measurement properties in a large sample of workers. This measure can be used to identify the mechanisms that place groups at increase risk of work injury. It can also be used to monitor change in OH&S vulnerability over time. Abstract: Injuries at work have a substantial economic and societal burden. Often groups of labour market participants, such as young workers, recent immigrants or temporary workers are labelled as being "vulnerable" to work injury. However, defining groups in this way does little to enable a better understanding of the broader factors that place workers at increased risk of injury. In this paper we describe the development of a new measure of occupational health and safety (OH&S) vulnerability. The purpose of this measure was to allow the identification of workers at increased risk of injury, and to enable the monitoring and surveillance of OH&S vulnerability in the labour market. The development included a systematic literature search, and conducting focus groups with a variety of stakeholder groups, to generate a pool of potential items, followed by a series of steps to reduce these items to a more manageable pool. The final measure is 29-item instrument that captures information on four related, but distinct dimensions, thought to be associated with increased risk of injury. These dimensions are: hazard exposure; occupational health and safety policies and procedures; OH&S awareness; and empowerment to participate in injury prevention. In a large sample of employees in Ontario and British Columbia the final measure displayed minimal missing responses, reasonably good distributions across response categories, and strong factorial validity. This new measure of OH&S vulnerability can identify workers who are at risk of injury and provide information on the dimensions of work that may increase this risk. This measurement could be undertaken at one point in time to compare vulnerability across groups, or be undertaken at multiple time points to examine changes in dimensions of OH&S vulnerability, for example, in response to a primary prevention intervention.